Knowledge, Attitude and Practice regarding Tuberculosis among Diabetic Patients (BIRDEM Medical Journal, 2017)
Background: Tuberculosis (TB) is a major public health problem in Bangladesh. This study aimed to evaluate the current status of the knowledge, attitude, and health-seeking practice regarding TB amongst diabetic patients.Methods: This cross-sectional study was done in the Pulmonology OPD of Department of Internal Medicine, BIRDEM, 750 bedded Specialized Diabetic Tertiary Care hospital, Dhaka, Bangladesh from January to December 2015.Results: Out of 420 subjects (mean ±SD, age 51±12 years), 51% were male. Regarding educational status, 42% had primary and 34% had secondary education, while 12% graduated and 12% never attended school. More than half of the subjects belonged to the lower-middle income group. The proportion of poor, average and good score for knowledge were 19%, 66% and 15%, attitude 6%, 42% and 52% and for practice 11%, 82% and 7% respectively.Conclusion: Co-ordinated educational campaign with prioritized focus for poorer and less educated people needs to be considered for reducing tuberculosis transmission and better outcome with special attention to diabetic population.Birdem Med J 2017; 7(2): 127-131